Design and implementation of a millirobot for swarm studies – mROBerTO. Issue 11 (30th July 2018) - Kim, Justin Y.; Kashino, Zendai; Colaco, Tyler; Nejat, Goldie; Benhabib, Beno
SUMMARY: The use of millirobots, particularly in swarm studies, would enable researchers to verify their proposed autonomous cooperative behavior algorithms under realistic conditions with a large number of agents. While multiple designs for such robots have been proposed, they, typically, require custom-made components, which make replication and manufacturing difficult, and, mostly, employ non-modular integral designs. Furthermore, these robots' proposed small sizes tend to limit sensory perception capabilities and operational time. Some have resolved few of the above issues through the use of extensions that, unfortunately, add to their size. In contribution to the pertinent field, thus, a novel millirobot with an open-source design, addressing the above concerns, is presented in this paper. Our proposed millirobot has a modular design and uses easy to source, off-the-shelf components. The m illi- r obot- T oronto ( mROBerTO ) also includes a variety of sensors and has a 16 × 16 mm 2 footprint. mROBerTO 's wireless communication capabilities include ANT ™, Bluetooth Smart, or both simultaneously. Data-processing is handled by an ARM processor with 256 KB of flash memory. Additionally, the sensing modules allow for extending or changing the robot's perception capabilities without adding to the robot's size. For example, the swarm-sensing module, designed to facilitate swarm studies, allows for measuring proximity and bearing to neighboring robots and performing local communications. Extensive experiments, some of which are presented herein, have illustrated the capability of mROBerTO units for use in implementing a variety of commonly proposed swarm algorithms.